PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA DAN DISIPLIN KERJA SEBAGAI VARIABEL MEDIASI PADA DINAS LINGKUNGAN HIDUP (DLH) KABUPATEN MERAUKE PROVINSI PAPUA SELATAN - O. Kotanon, Maris Stella; M. Alhadar, Fadhliah; Soleman, Marwan Man (Jurnal Manajemen Sinergi, 2023)
ABSTRACTObjective: This research aims to determine the influence of product quality and price on purchasing decisions mediated by word of mouth in the case of the Puta Dino Tidore weaving house.The sample size for this research was 49 employees at the Environmental Service (DLH) of Merauke District, South Papua Province.Methodology: Â The analysis test tool uses SEM-Smart-PLS.Findings: Partial hypotheses and simultaneous and partial hypotheses are accepted, because the alpha value is smaller than 5%.Conclusion: The results of this research show that: (1) job satisfaction has a positive and significant effect on employee performance; (2) job satisfaction has a positive and significant effect on work motivation; (3) job satisfaction has a positive and significant effect on work discipline; (4) work motivation has a positive and significant effect on employee performance; (5) work discipline has a positive and insignificant effect on employee performance; (6) positive and significant work motivation as a mediating relationship between job satisfaction and employee performance; (7) work discipline is positive and not significant as a relationship between job satisfaction and employee performance.